The effects of macroeconomic policies under fixed exchange rates: A Bayesian VAR analysis - Tevdovski, Dragan; Petrevski, Goran; Bogoev, Jane (Informa UK Limited, 2019)
We analyse the effects of fiscal and monetary policies in Croatia and Macedonia estimated by a Bayesian vector autoregression (VAR). The main results of the study are as follows. Fiscal tightening leads to economic expansion in Macedonia and a decline in economic activity in Croatia. In both countries fiscal tightening leads to a decline in inflation and money market rates. Monetary tightening leads to output contraction and a decline in inflation in both countries. We find an opposite reaction of the fiscal authorities to a monetary shock, i.e., monetary contraction is accompanied by fiscal tightening in Croatia and by loose fiscal policy in Macedonia.
Keywords: Fiscal policy, monetary policy, Bayesian VAR